2017
DOI: 10.1136/annrheumdis-2017-211216
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and polymyalgia rheumatica occurring after immune checkpoint inhibitor treatment

Abstract: This is the first description of RA occurring after ICI therapy for cancer. PMR can also occur after ICI, particularly after anti-PD-1 therapy. All cases responded to corticosteroids or with immunosuppressive therapy. Collaboration between rheumatologists and oncologists is crucial and could lead to better recognition and care of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
134
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(148 citation statements)
references
References 23 publications
8
134
3
3
Order By: Relevance
“…When needed, methotrexate was added, which was the case for two patients. In our experience, as in the series reported by Belkhir et al ,16 classical anti-inflammatory treatment was able to control rheumatic disorders without any modification of the ICI regimen, conversely to the experience of American colleagues, who reported a requirement for higher steroid dosage (often >40 mg/day), the use of tumour necrosis factor inhibitors for some patients and usually ICI discontinuation 14 15. Furthermore, the increasing number of cases reported in the literature illustrates these differences regarding rheumatic irAE management, highlighting the need for developing either national or international recommendations.…”
Section: Discussionsupporting
confidence: 70%
“…When needed, methotrexate was added, which was the case for two patients. In our experience, as in the series reported by Belkhir et al ,16 classical anti-inflammatory treatment was able to control rheumatic disorders without any modification of the ICI regimen, conversely to the experience of American colleagues, who reported a requirement for higher steroid dosage (often >40 mg/day), the use of tumour necrosis factor inhibitors for some patients and usually ICI discontinuation 14 15. Furthermore, the increasing number of cases reported in the literature illustrates these differences regarding rheumatic irAE management, highlighting the need for developing either national or international recommendations.…”
Section: Discussionsupporting
confidence: 70%
“…While the early clinical series3 18 of rheumatic irAEs failed to demonstrate the presence of autoantibodies in patients with inflammatory polyarthritis, several recent reports suggest that pre-existing autoantibodies such as anticitrullinated protein antibodies5 and diabetes-associated islet antibodies19 may be predictive of new-onset rheumatoid arthritis and type 1 diabetes. Thus, efforts to profile risk for incident irAEs prior to checkpoint therapy need to be explored and specialists such as rheumatologists may be logical partners to monitor and manage such complications before they occur.…”
mentioning
confidence: 99%
“…Recent studies have shown that immune checkpoint inhibitors which are immunostimulatory in nature are associated with PMR development which was reported in four cases and where PMR responded to standard therapy 29. Off note, the most severe toxicity in the checkpoint inhibitor class of drugs including anti-CTLA-4 and anti-programmed cell death protein 1 (PD-1) and anti-PD-L1 is gut toxicity and this is more common with anti-CTLA-4 30.…”
Section: Discussionmentioning
confidence: 95%